The Implementation Of Discovery Learning Model To Improve Students’ Learning Activities and Cognitive Abilities Of SMP Negeri 1 Wakorumba Utara - Rosman Sadat (Journal of Biological Science and Education, 2019)
This study aims to improve student learning activities and cognitive abilities through discovery learning model on the material characteristics and classifications of living creatures in class VII 1 of SMP Negeri 1 Wakorumba Utara. This research was conducted in the 2nd semester of the academic year 2015/2016. This type of research is Classroom Action Research (CAR) with three learning cycles. Each cycle goes through four stages: (1) planning; (2) implementing actions; (3) observation and (4) reflection. The data source of this study was an assessment using observation sheets of student learning activities, evaluation questions as tests of cognitive abilities and observation sheets of teacher activities in cycle I, cycle II and cycle III. The data obtained were analyzed using descriptive analysis. The success of the learning activities of the students in cycle I achieved a mean score of 3.1, cycle II 3.5 and cycle III 3.5. The average achievement of the cognitive abilities of students in the first cycle was 66.36. Cycle II was 79.09 and Cycle III was 78.18. The mean achievement of teacher activity in the first cycle was 3.2, the second cycle was 3.6 and the third cycle was 3.7. Based on the results of the study concluded that the application of discovery learning models can improve learning activities and cognitive abilities of students on the subject matter of the characteristics and classifications of living creatures of class VII1 students of SMP Negeri 1 Wakorumba Utara.                                                   Keywords:  Discovery Learning Model, Student Learning Activities, Student Cognitive Abilities